2019
DOI: 10.1108/ijes-05-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, biological, radiological, nuclear and explosive (CBRNe) events

Abstract: To systematically review published literature for the research question 'what issues are considered (and changes made) for vulnerable groups as part of the Chemical. Biological, Radiological, Nuclear or explosive (CBRNe) response for casualty collection, decontamination, triage and casualty clearing processes?' Design: Seven-stage framework from the PRISMA statement for research question, eligibility (definition), search, identification of relevant papers from title and abstract, selection and retrieval of pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This study synthesized WAI and WAD and identified phases of the ED CBRN response in line with previous literature 50 consisting of general phases (initial response, consolidation phase, and recovery phase) for hospitals responding to major incidents (including CBRN events) and the following: Evacuation Triage Decontamination for vulnerable individuals during CBRN emergencies 51 …”
Section: Discussion and Recommendationsmentioning
confidence: 87%
See 1 more Smart Citation
“…This study synthesized WAI and WAD and identified phases of the ED CBRN response in line with previous literature 50 consisting of general phases (initial response, consolidation phase, and recovery phase) for hospitals responding to major incidents (including CBRN events) and the following: Evacuation Triage Decontamination for vulnerable individuals during CBRN emergencies 51 …”
Section: Discussion and Recommendationsmentioning
confidence: 87%
“…Triage 3. Decontamination for vulnerable individuals during CBRN emergencies 51 Categorizing CBRN actions into phases allows the streamlining of an effective CBRN response, for example, by preparing for the arrival of casualties in line with previous findings 52,53 as a means of freeing resources to deal with the surge of casualties.…”
Section: Confirmabilitymentioning
confidence: 99%
“…This study aimed to examine the impact of a longitudinal structured evaluation process on the capacity to build and maintain effective emergency preparedness for severe but infrequent risks over time. It has been previously stated that an ongoing evaluation process facilitates improvement of emergency preparedness for 'conventional' MCIs [39], but this has not as yet been sufficiently demonstrated as effective in CBRN events [9,38]. For this purpose, the preparedness of hospitals for a mass casualty incident that involved hazardous materials was chosen and evaluated over a period of a decade.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 11 September 2001 attack in the USA, the interest of governing authorities, as well as of the media and the public, expanded to include chemical and toxicological threats [6]. Many states invest significant resources in building their capacity to manage such events and mitigate their consequences, but nonetheless, it has been stated that such efforts have been too limited and, as of yet, many deficiencies in the level of emergency preparedness are still predominant [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear, radiological, chemical, and biological weapons of mass destruction exist. They are a threat when used by a state in war, by an organization, or by an individual perpetrator in a terrorist attack [ 13 , 14 ]. All types of mass destruction weapons are regulated by international treaties, and there is an effort to ban or at least restrict their possession.…”
Section: Toxins As a Part Of Biological Warfare Agentsmentioning
confidence: 99%